A Short Review on Mesoporous Silica-Supported Catalysts for Methane Dry Reforming - Singh, Sharanjit; Omoregbe, Osaze; Tan, Ji Siang; Fayaz, Fahim; Vo, Dai-Viet N. (Universiti Malaysia Pahang, 2016)
The aim of this review is to gain a better insight in to the recent developments made in mesoporous silica molecular sieves, such as MCM-41, SBA-15, and SBA-16, as supports for dry reforming of methane. It further explored how different constraints such as the synthesis method for the mesoporous materials and techniques for metal loading on the mesoporous materials influence the dry reforming reactions and products yields. The high surface area and 2D hexagonal arrays of MCM-41 and SBA-15, 3D cage like structure of SBA-16 allow for good dispersion of metals inside their channels, which in turn, facilitates high catalytic activity and less catalyst deactivation. In this review, attention will be given to different strategies for enhancing catalytic activities, and the effect of metal dispersion on mesoporous silica supports.